(untitled) (Research, Society and Development, 2023)
Hairy cell leukemia (HCL) is a very rare type of B-cell cancer characterized by the presence of hairy cells in peripheral blood and bone marrow. It mainly affects adult males with a median age of 50 years. Hairy cells are positive for tartrate-resistant acid phosphatase (TRAP) staining and express surface markers CD11c, CD20, CD22, CD25, and CD103. The identification of the BRAF V600E mutation in 2016 has provided a notable diagnostic tool, found in almost 80% of all HCL patients. Currently, the possibility of a multiparametric approach to diagnosis is opening up. Clinical case: A 78-year-old man presents symptoms of marked asthenia, adynamia, hyporexia, and unquantified weight loss, as well as a feeling of gastric fullness. Physical examination reveals a globular, distended abdomen and a palpable splenomegaly of 6 cm, without adenopathies or hepatomegaly. Controlled hypertensive history. He works in agricultural tasks and is frequently in contact with insecticides and pesticides. Conclusion: HCL commonly presents with pancytopenia, splenomegaly, and monocytopenia, characterized by the presence of medium-sized lymphoid cells with broad cytoplasm and cytoplasmic projections that give a hairy appearance in peripheral blood. Diagnosis is established through clinical symptoms, bone marrow aspiration and biopsy, flow cytometry, and other complementary tests.words: Leukemia, Hairy Cell, Flow Cytometry, Bone Marrow, Cell Cycle, Epigenomics.